2014
DOI: 10.1177/0886260514554422
|View full text |Cite
|
Sign up to set email alerts
|

Protective Informal Social Control of Child Maltreatment and Child Abuse Injury in Seoul

Abstract: Previous findings on the relationship between neighborhood informal social control and child abuse have been mixed. We implemented a scale created by Emery, Trung, and Wu to study protective informal social control of child maltreatment (ISC_CM) by neighbors in a three-stage random cluster sample of 541 families in Seoul, South Korea. Random-effects regression models found that protective ISC_CM significantly moderated the relationship between very severe abuse and child injuries. Very severe abuse was associa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
35
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 38 publications
(41 citation statements)
references
References 17 publications
3
35
3
Order By: Relevance
“…Of the 100 men in the survey, 7 (7%) reported perpetrating some physical IPV against their spouses in the past year. This is not significantly different (Z = 1.32, p = .19) from the 11.5% IPV by fathers in the last year found in Emery et al's () study of Seoul. Of the men in the sample, 14 (14%) reported perpetration of severe physical child abuse in the past year.…”
Section: Resultscontrasting
confidence: 59%
See 1 more Smart Citation
“…Of the 100 men in the survey, 7 (7%) reported perpetrating some physical IPV against their spouses in the past year. This is not significantly different (Z = 1.32, p = .19) from the 11.5% IPV by fathers in the last year found in Emery et al's () study of Seoul. Of the men in the sample, 14 (14%) reported perpetration of severe physical child abuse in the past year.…”
Section: Resultscontrasting
confidence: 59%
“…Of the 100 men in the survey, 7 (7%) reported perpetrating some physical IPV against their spouses in the past year. This is not significantly different (Z = 1.32, p = .19) from the 11.5% IPV by fathers in the last year found in Emery et al's (2014) A serious concern with respect to this sample is selection bias given the low response rate. Fortunately, the five administrative districts in this study were included in a much larger study of IPV in Seoul conducted in 2012, for which we have data access.…”
Section: Resultscontrasting
confidence: 54%
“…Likewise, when very severe abuse did occur, protective ISC_CM was associated with fewer abuse-related externalizing behavior problems. Using the same scale, Emery et al (2015a) found protective ISC_CM was negatively associated with physical abuserelated injuries. Emery et al (2015b) found that acts of protective informal social control of intimate partner violence carried out by neighbors were negatively associated with physical child abuse severity.…”
Section: Informal Social Control Of Child Maltreatment: Isc_cmmentioning
confidence: 96%
“…Analyses of collective efficacy and physical abuse in Sampson et al's Chicago data (1997) found no relationship (Molnar et al 2003). Studies of collective efficacy and physical abuse in the East Asian context found no relationship in Hanoi (Emery et al 2015c) or Seoul (Emery et al 2015a).…”
Section: Informal Social Control: Theory and Researchmentioning
confidence: 98%
See 1 more Smart Citation